Health Promoting Lifestyle profile Among Nursing Students in Mosul University - Hussein, Ahmed Ali; Younis , Nasir Muwfaq; Ahmed, Mahmoud Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Background: Health promotion, its enabling of individuals to improve of health and control of disease.Health has therefore been described as a positive pattern of action and not merely a pattern of disease avoidance (physiological, emotional, spiritual and social). Objectives: The aim of the research was to assess of health promoting lifestyle profit (HPLP) among undergraduates in Mosul City. Materials and Method: A descriptive research in January – February2020, Mosul/Iraq was performed. The tools use in this study consisted of (2) parts: Part I: demographic variables (age, gender, BMI, marital status and family income) and Part II: questions from (HPLP). Results: The study participants (280) nursing students, of which (40%) were male, while (60%) were female. The total mean of the Health Promoting Lifestyle was (123.2 ± 19.9). Consequence of the study demonstrate the health promotion behavior differed by gender, especially regarding social relationships, physical activity. Conclusion: The consequences of the study indicated that the health lifestyle promotion differed by gender, especially in terms of interpersonal relationships and physical activity, and the researcher found that many nursing students had a serious problem with their health behavior and lifestyle.